PENGEMBANGAN MEDIA ANIMASI BERBASIS CANVA UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS V SD (STUDI LITERATUR) - Fadia Nabila, Siti; Sakmal, Juhana; Dallion, Engga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the benefits of digital audio-visual learning media in the form of animation (canva) to improve the skills of writing narrative texts for grade V elementary school students. This research uses kuantitatif with literature study techniques. Data collection techniques are carried out by searching for scientific articles related to research. Animation media is a media that combines the senses of vision and hearing by displaying a moving image or video to increase student interest in learning. Based on data from 6 journal articles that have been analyzed, it can be concluded that Canva-based animation media can make a positive contribution in improving students' narrative text writing skills with reason, uniqueness, visual appeal, better understanding, creativity and exploration.